Middle Eastern and Indonesian Folktales as BIPA Teaching Materials: Structural Analysis and Cultural Values - Elvi Zurviana; Halimah Halimah; Yulianeta Yulianeta; Isah Cahyani (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Folktales are a cultural heritage that can be used as intercultural teaching materials in BIPA (Indonesian Language for Foreigners) 4 learning. This study aims to integrate Indonesian and Middle Eastern cultures in BIPA learning through a structural analysis of folktales from the two countries. The background of this study is based on the urgency of introducing cultural values ​​in language learning. The context of language teaching does not only emphasize linguistic aspects, but also it requires sociocultural aspects. Using qualitative descriptive methods and AJ. In Greimas' structural analysis, this study examined the story content, narrative structure, and cultural values ​​in Middle Eastern folktales: Ali Baba and the Forty Thieves, Aladdin and the Magic Lamp, and Sinbad the Sailor. And Indonesian folktales: Si Pitung, Timun Mas, Keong Mas. The research findings showed that both groups of folktales have relevant cultural values ​​to be internalized in the reading and cultural insight aspects of BIPA 4 learners. Cultural values such as courage, hard work, and ingenuity appear consistently in the characters and storylines. This study contributes to strengthening cultural education through language learning as an attempt to internalize Indonesian through a culture-based approach, and becoming a medium for cross-cultural teaching.